Effects of the direct thrombin inhibitor dabigatran on ex vivo coagulation time in orthopaedic surgery patients: a population model analysis - Liesenfeld, Karl‐Heinz; Schäfer, Hans G.; Trocóniz, Iñaki F.; Tillmann, Christiane; Eriksson, Bengt I.; Stangier, Joachim (British journal of clinical pharmacology, 2006)
Aims To describe the pharmacokinetic–pharmacodynamic (PK–PD) characteristics of the direct thrombin inhibitor dabigatran in hip replacement patients by assessing coagulation parameters activated partial thromboplastin time (aPTT) and ecarin clotting time (ECT), interindividual variability and factors affecting PD responses. Methods BISTRO I patients received oral dabigatran etexilate postsurgery for 6–10 days. Dabigatran plasma concentrations and aPTT/ECT were measured on the day of surgery, on subsequent days and at steady state. PK–PD characteristics of the dabigatran–aPTT/ECT relationships were evaluated using NONMEM V. Results The dabigatran concentration–aPTT relationship was described combining a linear and an Emax model. Mean baseline aPTT was 33.4 s and Emax (maximum increase in aPTT contributed by the Emax model) was 26.9 s. The dabigatran concentration needed to attain 50% of maximum effect (EC50) was 94.7 ng ml−1 and the mean slope of the linear concentration–response relationship (SLOP) was 0.0509 s ng−1 ml−1. Baseline aPTT and Emax were highest following surgery and declined with time. The dabigatran concentration–ECT relationship fitted a linear model. Mean baseline ECT was 28 s and decreased with time; 50% of the maximum effect was observed after 2.9 days. SLOP decreased from 0.38 to 0.27 s ng−1 ml−1 with a half‐life of 1.1 day, indicating greater PD effects on the day of surgery. Interindividual and residual variability was low. Covariates could not explain variability of this model. Conclusions aPTT and ECT prolongation were directly correlated with dabigatran concentrations. Blood coagulation prolongation was most pronounced following surgery. Data suggest that ECT provides a more precise description of the anticoagulant effect than aPTT.